PENGENALAN POTENSI DESA BANDUNGREJO MELALUI PENYUSUNAN BOOKLET ONLINE SEBAGAI MEDIA PROMOSI - Ibnu Rosyid Ridwana; Alya Najla Khairunnisa; Risky Putri Kusumastuti; Rien Gladys Kusuma Andini; Ria Ivana Devi; Husna Khoirunnisa; Rofi'ur Rohman; Rizqi Hanung Handika; Devanda Adrian Ardistya; Hani Dwi Rahma Yulizar; Atika Nur Hidayah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Bandungrejo Village, located in Ngablak District, Magelang Regency, has various village potentials, including natural resources, horticultural agriculture, and distinctive local arts and culture. However, these potentials have not been optimally utilized due to limited integrated promotional media and the low use of digital technology in information dissemination. This condition has resulted in low tourist visitation and limited economic benefits from the tourism sector for the local community. This article is an output of a Community Service Program (Kuliah Kerja Nyata/KKN) aimed at documenting and describing the implementation of an online booklet development as a promotional medium for Bandungrejo Village’s potential. The activity employed a Participatory Action Research (PAR) approach, with data collected through field observations, interviews with village officials, tourism managers, and community leaders, as well as documentation studies of village profiles and supporting data. The implementation stages included identifying and analyzing village potential, coordinating and planning concepts with community partners, producing narrative and visual content, designing and digitalizing the booklet, and distributing it through digital media using links and QR codes. The results indicate that the online booklet effectively presents village potential in a systematic, informative, and easily accessible manner. The availability of this online booklet is expected to enhance the visibility of Bandungrejo Village, strengthen its image as a nature- and culture-based tourism destination, and serve as a sustainable promotional tool for village authorities and tourism management groups in supporting rural tourism development.